Family reciprocity of older Singaporeans - Verbrugge, Lois M. (2019)
Reciprocity is a powerful motivation in social life. We study what older people give to their family for help received. Data are from the Panel on Health and Aging of Singaporean Elderly, Wave 2 (2011; persons aged 62+; N = 3103). Giving and receiving help are with family members other than spouse in the same household, in the past year. Types of help given and received are money, food/clothes/other material goods, housework/cooking, babysitting grandchildren, emotional support/advice, help for personal care, and help for going out. Multivariate models predict each type of giving help, with independent variables about the older person’s resources, needs, and help received. Reciprocity is demonstrated by positive relationships between receiving and giving help. Results show two kinds of reciprocity: “nontangibles for tangibles” and “same for same.” First, older people give their time and effort in return for money and material goods. This aligns with contemporary Singapore circumstances, in that older people tend to have ample time but limited financial resources, while family members (often midlife children) have the reverse. Second, same-for-same exchanges, such as housework both given and received, are shared tasks in families or normative behaviors in Singapore society. The results replicate and extend prior ones for Singapore. We discuss prospects for change in frequency and shape of family reciprocity as the state continues to modernize.